2018
DOI: 10.1002/jid.3392
|View full text |Cite
|
Sign up to set email alerts
|

Role of Art Education in Peace Building Efforts among Out‐of‐School Youth affected by Armed Conflict in Zamboanga City, Philippines

Abstract: This article looks into the value of art education in helping out‐of‐school adolescents to reintegrate to the local community due to armed conflicts in Zamboanga City, Southern Philippines. Using focus group discussion, which was carried out with adolescents living in transitory sites, permanent shelters and informal settlements in the city, findings have revealed that participants in the programme gained knowledge, developed positive attitude and communication skills and practiced peace building behaviours th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Introduction Even though it has been happening for a long time, the use of art to build peace has been attracting growing interest in the field of peace and conflict since the 1990s. In the context of the increasing focus on 'internal wars' (Bergh and Sloboda, 2010), 'everyday peacebuilding' and the 'local turn' (Bleiker, 2009;Kim, Kollontai and Yore, 2016;Labor, 2018;Rizzolo and Schuler, 2003;Zelizer, 2003), scholars and practitioners acknowledge the potential of art to transform conflicts and build peace. They highlight the ways in which art initiatives can contribute to healing, building peaceful environments, stimulating creativity for peacebuilding and building bridges and bringing people together by valuing and harnessing differences to move beyond othering (Marshall, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Introduction Even though it has been happening for a long time, the use of art to build peace has been attracting growing interest in the field of peace and conflict since the 1990s. In the context of the increasing focus on 'internal wars' (Bergh and Sloboda, 2010), 'everyday peacebuilding' and the 'local turn' (Bleiker, 2009;Kim, Kollontai and Yore, 2016;Labor, 2018;Rizzolo and Schuler, 2003;Zelizer, 2003), scholars and practitioners acknowledge the potential of art to transform conflicts and build peace. They highlight the ways in which art initiatives can contribute to healing, building peaceful environments, stimulating creativity for peacebuilding and building bridges and bringing people together by valuing and harnessing differences to move beyond othering (Marshall, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the article by Rauduvaite and Yao [62], based on the research of Vasiliauskas [99], emotions are an important component in the structure of values. Likewise, Labor [65] indicates that exposure to arts programs has led to the formation of upright attitudes and positive practices [100][101][102]. In the article by Rauduvaite and Yao [62], students who have worked in theatre develop positive attitudes and a willingness to act and be part of an environmental change.…”
Section: The Arts In the Development Of Character Strengths In Positi...mentioning
confidence: 99%
“…In the article by Rauduvaite and Yao [62], students who have worked in theatre develop positive attitudes and a willingness to act and be part of an environmental change. Studies by Labor [65] have also revealed that participants in an arts program acquire knowledge, develop positive attitudes and communication skills and practice peacebuilding behaviors. In short, the objective of artbased methods is, like that of competency focused education, to strengthen self-knowledge and a positive self-concept and to analyze life, its phenomena, and the relationship of oneself with these [75].…”
Section: The Arts In the Development Of Character Strengths In Positi...mentioning
confidence: 99%
“…Among the most significant effects of art we will highlight such as the development of personality creative potential, ethical principles and aesthetic ideals, socio-cultural children and youth adaptation to prevent, if necessary, correct antisocial behaviour, form a culture of interethnic communication and respect for the world different nations artistic traditions (Labor, 2018;Clarke & Basilio, 2018).…”
Section: Problem Statementmentioning
confidence: 99%